THE CORRELATION BETWEEN SIMPLE PRESENT TENSE MASTERY AND WRITING ABILITY IN SELF-INTRODUCTION TEXTS OF FEMALE AND MALE STUDENTS - Luluk Safira Ikrima; Suprihadi Suprihadi; Nuraeningsih Nuraeningsih (Prominent, 2020)
Grammar is very important in learning and using languages so that using correct grammar will indicate clearly what the writer says. The objective of this research is to find out if the correlation between simple present tense mastery and writing ability in self-introduction texts of the tenth grade students of SMK N 1 Kalinyamatan Jepara is  1) significant for female students, and 2) not significant for male students. This correlational research was conducted in SMKN 1 Kalinyamatan Jepara with 30 students from Class X Tata Boga 2 (BG 2) for female and 30 students from Class X Teknik Elektronika Industri 1 (EI 1) for male as the samples. Pearson Product Moment Correlation was used to analyze the data. The findings show that the correlation of simple present tense mastery and writing ability in self-introduction texts of female students is significant while that of male students is not significant.